1999
DOI: 10.1590/s0102-76381999000300002
|View full text |Cite
|
Sign up to set email alerts
|

Plástica da valva mitral: resultados aos 17 anos de experiência

Abstract: RESUMO: Foram analisados 545 pacientes submetidos a 560 plásticas da valva mitral no período de março de 1980 a dezembro de 1997. A idade variou de 3 meses a 86 anos com média de idade de 42,2 ± 21,4 anos. Duzentos e setenta e quatro (50,3%) pacientes eram do sexo masculino. A etiologia foi reumática em 234 (42,9%) pacientes. As técnicas utilizadas foram: ressecção quadrangular da cúspide posterior em 204 (36,5%) pacientes, anuloplastia com tira posterior de pericárdio bovino em 139 (24,5%) pacientes, anel de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Pomerantzeff et al 21 reported reoperationfree survival in 70% after 17 years 21 . Patients with rheumatic valve disease have had a high incidence of reoperation, as demonstrated by Deloche et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Pomerantzeff et al 21 reported reoperationfree survival in 70% after 17 years 21 . Patients with rheumatic valve disease have had a high incidence of reoperation, as demonstrated by Deloche et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in our country, rheumatic etiology is prevalent and, in this population, the long-term outcomes may be affected by the appearance of new outbreaks of the disease [7]. Despite this fact, every effort must be made in order to perform conservative treatment, since a large proportion of these patients are young and therefore subject to greater number of surgical interventions during evolution [8,9]. Other factors to be considered are the difficulty of anticoagulation of patients in our country and early calcification of bioprostheses in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Quadrangular resection associated with or not "sliding" repairs is the normal technique for this indication. Annuloplasty with a prosthetic ring to reestablish the format of the mitral valve orifice, in all chronic diseases of the aforementioned cases, is accepted by the majority of surgeons [11]. The tendency is to implant the largest ring possible, as implantation of the ring is not used to restrict the mitral valve surface, but to reshape the orifice [11].…”
Section: Commentsmentioning
confidence: 99%
“…These two techniques, used by many surgeons, present questionable limitations and results [8,9]. In our experience, we repair anterior leaflet prolapse with a reproducible and safe technique: papillary muscle repositioning (PMR) [10,11]. The aim of this study was to describe the technique and the results and to recommend this technique as the standard procedure.…”
Section: Introductionmentioning
confidence: 99%